PELATIHAN PEMBUATAN MEDIA BERDASARKAN SENTRA DI TK IT AZ-ZAHRA KABUPATEN ACEH TENGAH - Nst, Awal Kurnia Putra; Harahap, Rosliana; Ahmad, Nurul Qomariyah (LPPM Institut Pendidikan Nusantara Global, 2024)
Kindergarten is a form of preschool education that provides early education programs for children aged four years until they enter primary education. At this stage, students are still focused on playing. For this reason, teachers must have the ability to design a learning process that suits the students' conditions, but problems are found. Where teachers still experience difficulties in making appropriate central media, with central media teachers can make the learning process like playing but there is a process of transferring knowledge to students. Because of the importance of central media at the Kindergarten Level, the service TEAM carries out training in making central-based media in Kindergarten TK IT Az-Zahra. The service method uses the ABCD method. The results obtained from this activity are that teachers are able to create center-based media well and center-based learning media has advantages such as being able to build children's knowledge which is explored by the children themselves. By playing they gain knowledge.